Addition of niobium in Fe-13Cr-4.5Al-2Mo alloy used as ATF cladding: Effect on high temperature water corrosion and in-situ electrochemistry. (August 2022) - Liao, Jingjing; Wang, Hui; Wu, Jun; Zhang, Wei; Xu, Fei; Sun, Hongying; An, Xuguang; Qiu, Shaoyu
Graphical abstract: Highlights: Four Fe-13Cr-4.5Al-2Mo alloys with different Nb content were designed. In-situ electrochemistry was conducted to quantitatively verify corrosion behavior in 360 °C lithiated and borated water. Slight Nb addition benefits corrosion resistance due to larger oxide impedance and delayed oxidation of Fe2 Nb particles. Cathodic Tafel kinetics of in-situ polarization curves reveals the oxygen reduction mechanism on FeCrAl surface. Abstract: Niobium addition in candidate accident tolerant fuel (ATF) cladding FeCrAl alloy has received much attention, but its effect on high temperature water corrosion behavior has not been revealed. Four alloys with different Nb content (0 wt%, 0.5 wt%, 1.0 wt% and 1.5 wt%) based on Fe-13Cr-4.5Al-2Mo model alloy were designed, and the corrosion behavior was investigated by in-situ electrochemistry and microscopy. The in-situ electrochemistry analyses, including open circuit potential (OCP), polarization and electrochemical impedance spectrum, were carried out in 360 °C/19.0 MPa lithiated and borated water connected with a loop system to monitor the water chemistry. The oxide films formed after immersion for 85 days were deeply investigated by focused ion bombarding and transmission electron microscopy. Results have shown that OCP decreased with elevated temperature and corrosion potential increased with time. FeCrAl alloys have satisfactory corrosion resistance because of small corrosion currents and thin oxide films. Only monolayer multicrystal spinel oxide forms on FeCrAl alloys. Slight Nb addition (0.5 wt% and 1.0 wt%) benefits the corrosion resistance due to relatively large impedance of oxide and delayed oxidation of Fe2 Nb particles. Porosities with Fe depletion were spotted in oxide and especially severe in 1.5 wt%-Nb alloy. Cathodic Tafel kinetics and corrosion mechanisms of FeCrAl were further discussed.